PENGEMBANGAN USAHA UMKM DI MASA PANDEMI MELALUI OPTIMALISASI PENGGUNAAN DAN PENGELOLAAN MEDIA DIGITAL - Silviana Batubara; Fithra Maharani; Makhrani Makhrani (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has hit many countries, including Indonesia. Covid-19 has had an impact in various sectors including Micro, Small and Medium Enterprises, including a decline in sales. Community Service Activities are carried out to provide guidance in overcoming these impacts through the use and management of appropriate digital media. By using and managing digital media, it is hoped that business actors can determine the right type of digital media for the product being marketed, increasing public awareness and interest regarding the product. The method used is virtual training using Zoom Meeting. The material for this activity is a strategy for the use and management of digital media, optimization of digital marketing and product branding to improve the ability to create interesting content, promotion and as an alternative media for service businesses. The digital media used include Instagram, Facebook, WhatsApp, GrabFood/Go-Food, Tokopedia and other platforms. The results of the activity show that the training and guidance provided has a positive impact on business actors with an increase in knowledge about digital media, an increase in knowledge of various media that can be used and an increase in skills in the use and management of digital media in branding. Recommendations that can be conveyed are the existence of a sustainable development program for business actors so that they can implement and manage digital media optimally